Operant overtraining leads to increased Fos expression in IL and PL that is unaffected by fear conditioning - Pajser, Alisa (Kansas State University, 2019)
The fear incubation task is an extended training procedure used to cause low fear soon after training that grows over time. However, the neurobiological basis of this effect, particularly the low fear observed soon after training, is unknown. One possibility is that extended training leads to habituation to the shocks, so that the tone cue is repeatedly paired with ineffective shocks. If so, then the overtraining may lead to an effect similar to extinction, and the low fear seen soon after extended training may be associated with increased neuronal activity in the infralimbic cortex (IL), an area involved in extinction learning, and decreased neuronal activity in the prelimbic cortex (PL), an area involved in fear expression. The current study examined whether low fear soon after extended training is associated with increased IL and decreased PL activation, compared with rats given a single day of fear conditioning or no fear training. Male Long-Evans rats acquired lever-pressing and then underwent fear training for 1 or 10 days. During each fear training session, while lever-pressing on a VI60 schedule of reinforcement, half of the animals in each group received 10 30-second tones co-terminating with a 0.5-second foot-shock pseudo-randomly throughout each 90-minute session and half of the animals received the same tones with no shock. Two days later, animals underwent a cued fear test in which fear was measured using conditioned suppression of lever pressing. Brain tissue was extracted 120 minutes after the beginning of the test and subsequently processed using immunohistochemistry to target Fos, a protein marker of neuronal activation. As is typical with fear incubation, rats that underwent 10 days of fear conditioning exhibited lower fear than those that underwent 1 day of fear conditioning. There was no effect of shock on IL or PL Fos expression in either the 1 day or 10 day groups. However, both groups that received extended training (10 days) showed higher levels of Fos expression in IL and PL than the limited training (1 day) groups, regardless of whether the tones they experienced were paired with shock. My results suggest that, in our procedure, neither IL nor PL activity are associated with high fear after a single day of fear training or suppression of fear after extended fear training, or that any such association is undetectable with our procedures. However, our results also suggest that the extended lever-press training in our fear incubation procedure leads to increased IL and PL activity (possibly related to habit formation), and that the increased neuronal activity is unaffected by the co-occurring fear training and associated stress. Additional research will be needed to determine whether operant responding in our task would be insensitive to devaluation, and whether habit formation would be affected by co-occurring fear training. I will also analyze tissue (taken from rats in the current experiment) from the amygdala, a region known for its role in fear behaviors, for fear-related Fos expression.
Keywords: Fear conditioning; Habit learning; Operant overtraining; Infralimbic cortex; Prelimbic cortex; Fos